Detection of sebaceous gland hyperplasia with dermoscopy and reflectance confocal microscopy - Lin, Er-Yi; Rao, Lang; Wang, Wen-Ju; Chen, Yong-Feng (Frontiers in Medicine, 2023)
Background Sebaceous gland hyperplasia (SGH) is a benign cutaneous proliferation of the sebaceous glands that are mostly present on the face or the neck of older adults. They typically appear as single or multiple soft umbilicated papules; however, in challenging cases, it can be difficult to distinguish them from trichoepitheliomas, base cell carcinomas, or other tumors. Although pathological results have diagnostic value, the significance of non-invasive examinations in diagnosis and differential diagnosis is also worth exploring. Objectives This study aimed to describe the dermoscopic and reflectance confocal microscopy (RCM) features of SGH. Methods A total of 31 patients diagnosed with SGH, according to clinical and histopathological standards, were examined using dermoscopy and RCM between March 2018 and January 2022. Results Dermoscopically, lesions revealed a yellowish-red background and a faint-yellow background in 25 (80.65%) and six cases (19.35%), respectively. White-yellowish lobulated structures in the center of the lesion were present in 31 patients (100%) and umbilications in 19 patients (61.29%). Crown vessels at the periphery of the lesions were observed in 11 patients (35.48%), whereas irregular linear vessels were observed on the surface of the lesions in 18 patients (58.06%). Under RCM, all lesions presented a honeycomb pattern in the epidermis and the typical morulae-shaped sebaceous lobules in the dermis. A dilated follicular infundibulum was observed in 15 patients (48.39%) and dilated vessels in 26 patients (83.87%). Conclusion Dermoscopy and RCM enabled us to describe the imaging features of SGH. Combining these two useful tools provides a non-invasive basis for accurate clinical diagnosis.